James Alexander Robertson papers - Robertson, James Alexander, 1873-1939.
Correspondence, diaries, writings, notes, subject files, and other papers relating primarily to Robertson's activities and scholarship in Hispanic studies, especially relating to Florida and the Philippines. Documents his editorial work on the fifty-five volume "The Philippine Islands, 1493-1803," editorship of the Hispanic American Historical Review, role as executive secretary and editor of publications for the Florida State Historical Society, appointment as archivist of the State of Maryland, and travels to France, Italy, Portugal, and Spain from 1902 to 1907. Family correspondence relates to Robertson's work on the Philippines and to family affairs. Correspondents include Emma Helen Blair, Carroll T. Bond, James A. LeRoy, Irene Aloha Wright, and Robertson's wife, Cora Halsey Robertson.
Handwritten and typewritten transcripts, in part.
Library of Congress Prints and Photographs Division.
Library of Congress Serial and Government Publications Division.
Editor, bibliographer, and archivist.
Collection material in English, French, and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blair, Emma Helen, -- -1911 -- Correspondence; Bond, Carroll T. -- 1873-1943 -- Correspondence; LeRoy, James A. -- 1875-1909 -- Correspondence; Robertson, Cora Halsey, -- circa 1878- -- Correspondence; Wright, Irene Aloha, -- 1879-1972 -- Correspondence; Robertson family; Robertson family -- Correspondence; Maryland. -- Archives Division; Florida State Historical Society; Hispanic American historical review; Florida -- History; France -- Description and travel; Italy -- Description and travel; Latin America -- History; Latin America -- History -- Periodicals; Philippines -- History; Portugal -- Description and travel; Spain -- Description and travel; Archivists; Bibliographers; Editors